Penerapan Perhitungan PPH Pasal 21 Berdasarkan Undang – Undang Harmonisasi Peraturan Perpajakan Tahun 2021 Terhadap Take Home Pay Karyawan Tetap - Isnaini Azzahra; Fauziyah Fauziyah; Srikalimah Srikalimah (Jurnal Akuntan Publik, 2023)
The government passed Law on Harmonization of Tax Regulations no. 7 of 2021 In an effort to restore economic stability after the pandemic. In this provision, there are six changes regulated, one of which is regarding changes to the income tax rate in article 21. These changes in rates have been adjusted to reflect the conditions of society when facing the Covid-19 pandemic. The aim of this research is to analyze changes before and after the implementation of the Law on Harmonization of Tax Regulations in all Pizza Hut Branches in Kediri City. The method used in this research is descriptive quantitative with data collection techniques through observation and interviews. The results of the research show that the Take Home Pay of employees at Pizza Hut Restaurant according to the Law on Harmonization of Tax Regulations is IDR 154,555,773 and according to the Income Tax Law it is IDR 154,015,439. Meanwhile, at Pizza Hut Delivery Branch 2, the total employee take home pay according to the Law on Harmonization of Tax Regulations is IDR 119,712,095 and according to the Income Tax Law it is IDR 119,374,160. Take Home Pay for permanent employees with PKP below IDR 50,000,000 does not change because it is still within one layer of the tax rate. It is hoped that this research can contribute to companies in optimizing employee income tax calculations so that they can increase employee take home pay.